2003
DOI: 10.1680/muen.2003.156.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Driver distraction by advertising: genuine risk or urban myth?

Abstract: Drivers operate in an increasingly complex visual environment, and yet there has been little recent research on the effects this might have on driving ability and accident rates. This paper is based on research carried out for the Scottish Executive's Central Research Unit on the subject of external-to-vehicle driver distraction. A literature review/meta-analysis was carried out with a view to answering the following questions: is there a serious risk to safe driving caused by features in the external environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 5 publications
1
22
0
4
Order By: Relevance
“…Again there is limited research evidence regarding the effects of these features on bicycle crashes directly but it has been suggested that distracting elements such as advertising hoardings, road signs and the presence of other vehicles can cause reduced attention on driving tasks 173 . Cole and Jenkins have tried to give an operational definition of conspicuity which makes clear its importance for road safety research.…”
Section: Conspicuity and Bicycle Crashesmentioning
confidence: 99%
“…Again there is limited research evidence regarding the effects of these features on bicycle crashes directly but it has been suggested that distracting elements such as advertising hoardings, road signs and the presence of other vehicles can cause reduced attention on driving tasks 173 . Cole and Jenkins have tried to give an operational definition of conspicuity which makes clear its importance for road safety research.…”
Section: Conspicuity and Bicycle Crashesmentioning
confidence: 99%
“…by advertisement. Since for the advertising industry it is desirable that roadside advertisements gain a lot of attention, it can be a seen as source of distraction, increasing the complexity of drivers' visual environment (Wallace 2003). In the worst case this can result in a fatal accident.…”
Section: Attention In Guidance Systems and Driver-environmentsmentioning
confidence: 99%
“…In addition, a single distracter within the Ranney et al definition may belong to multiple categories; dialing a cell phone involves cognitive (remembering a telephone number), visual (scanning for the correct telephone button), and biomechanical (performing button presses) tasks. Considering both the source and the mechanism of distracters is especially useful as the number and variety of possible distraction sources increase (Wallace, 2003).…”
Section: Dr Iver Distr Actionmentioning
confidence: 99%